Extended thromboprophylaxis following major abdominal/pelvic cancer-related surgery: A systematic review and meta-analysis of the literature. Issue 204 (August 2021) - Knoll, William; Fergusson, Nathan; Ivankovic, Victoria; Wang, Tzu-Fei; Caiano, Lucia; Auer, Rebecca; Carrier, Marc
Abstract: Background: Postoperative venous thromboembolism (VTE) is a significant source of morbidity and mortality in cancer patients undergoing major abdominopelvic surgery. Many guidelines recommend the use of extended duration postoperative low molecular weight heparin (LMWH) thromboprophylaxis, although the evidence for its overall safety and efficacy is unclear. Aims: We sought to assess the 30-day postoperative rates of VTE and bleeding complications following major abdominopelvic cancer surgery and to explore the potential risks and benefits of extended duration thromboprophylaxis with LMWH in such setting. Methods: A systematic search of the literature was conducted. Observational studies and RCTs of adult patients that underwent abdominopelvic cancer surgery were included. Pooled proportions for the outcome measures and pooled relative risks for the extended duration thromboprophylaxis analyses were generated. Results: A total of 68 studies (1, 631, 118 patients) were included in the analysis. The 30-day postoperative rate of VTE was 1.7% (95%CI: 1.5 to 1.9, I 2 = 98%). The postoperative rate of clinically-relevant bleeding complications was 3.5% (95%CI: 1.6 to 6.1, I 2 = 99%). Extended duration thromboprophylaxis was associated with a significant reduction in the incidence of clinical VTE (1.0% vs 2.1%; Risk ratio (RR) 0.48, 95%CI: 0.31 to 0.74; I 2 = 0), without a significant increase in clinically-relevant bleeding (4.0% vs. 4.9%; RR 1.0, 95%CI: 0.66 to 1.5, I 2 = 0). Conclusions: The overall risk of symptomatic VTE within 30 days of surgery was relatively low. Extended LMWH thromboprophylaxis following major abdominopelvic cancer surgery was associated with a reduced incidence of clinical VTE without an increase in clinically-relevant bleeding. Highlights: The risk of venous thromboembolism is relatively low after major abdominopelvic surgery. Extended LMWH thromboprophylaxis reduced incidence of clinical VTE. Extended LMWH thromboprophylaxis does not increase the risk of bleeding.